2020
DOI: 10.1186/s12877-020-01923-y
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indicators as a discriminator of sarcopenia in community-dwelling older adults of the Amazon region: a cross-sectional study

Abstract: Background Sarcopenia is a geriatric syndrome associated with negative health outcomes and the use of viable alternative screening tools may help in the diagnosis of this condition. This study aimed to analyze the association of sarcopenia with anthropometric indicators among community-dwelling older adults and to identify cut-off points for such indicators as a discriminant criterion for predicting sarcopenia. Methods This was a cross-sectional study conducted on community-dwelling older adults ≥60 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 45 publications
4
26
2
18
Order By: Relevance
“…A recent study of community-dwelling older adults in Brazil reported that among anthropometric indicators including MUAC, waist circumference, CC, and BMI, MUAC (≤27 cm for both sexes) showed the best performance for identifying older adults with sarcopenia, with a sensitivity and specificity of 100% and 77.34%, respectively, for men and 100% and 70.54%, respectively, for women. 17 Another study that used corrected arm muscle area to detect sarcopenia according to EWGSOP2 criteria in older adult women found that the optimal cutoff value of corrected arm muscle area was 27.1 cm 2 . 18 However, in the above studies, muscle mass was calculated using the anthropometric prediction equation rather than recommended methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of community-dwelling older adults in Brazil reported that among anthropometric indicators including MUAC, waist circumference, CC, and BMI, MUAC (≤27 cm for both sexes) showed the best performance for identifying older adults with sarcopenia, with a sensitivity and specificity of 100% and 77.34%, respectively, for men and 100% and 70.54%, respectively, for women. 17 Another study that used corrected arm muscle area to detect sarcopenia according to EWGSOP2 criteria in older adult women found that the optimal cutoff value of corrected arm muscle area was 27.1 cm 2 . 18 However, in the above studies, muscle mass was calculated using the anthropometric prediction equation rather than recommended methods.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Additionally, MUAC and corrected MUAC were inversely associated with sarcopenia and could be used as alternative indicators to identify sarcopenia in community-dwelling older adults in Brazil. 17 , 18 However, the accuracy of MUAC to predict ASM index (ASMI) among Chinese community-dwelling older adults is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Participant accrual, attrition, program adherence, reasons for missed sessions, and adverse events will be documented. Body composition measures will include body mass index (kg/m 2 ), arm circumference, waist circumference, calf circumference [ 57 , 58 ], and muscle mass and quality. Muscle density and intramuscular adipose tissue will be assessed using whole-body MRI [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…The maximum arm circumference was recorded. AC is considered to be an indicator that can detect the loss of muscle mass in older adults [35]. Both CC and AC are strongly correlated with lean mass, and thus can be used to evaluate malnutrition in older people [36].…”
Section: Variablesmentioning
confidence: 99%